2016
DOI: 10.1051/matecconf/20164704004
|View full text |Cite
|
Sign up to set email alerts
|

Accidents Preventive Practice for High-Rise Construction

Abstract: Abstract. The demand of high-rise projects continues to grow due to the reducing of usable land area in Klang Valley, Malaysia. The rapidly development of high-rise projects has leaded to the rise of fatalities and accidents. An accident that happened in a construction site can cause serious physical injury. The accidents such as people falling from height and struck by falling object were the most frequent accidents happened in Malaysian construction industry. The continuous growth of high-rise buildings indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 18 publications
2
40
0
3
Order By: Relevance
“…The frequency with which the sampled companies verify the on-site risks and safety is, 22.0% at the start of a job, 19.0% at the beginning and the end of a job, and 19.0% at the start and daily. Accordingly, Goh and collaborators reported that exhaustive maintenance has to be performed along with periodic safety inspections [ 27 ], continuous safety training and the development of a plan to investigate accidents to prevent future injury; consequently, there are companies that not only possess such controls but that point them out as much as possible, in order to give them greater relevance among companies that work transparently and wish to gain greater legitimacy [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency with which the sampled companies verify the on-site risks and safety is, 22.0% at the start of a job, 19.0% at the beginning and the end of a job, and 19.0% at the start and daily. Accordingly, Goh and collaborators reported that exhaustive maintenance has to be performed along with periodic safety inspections [ 27 ], continuous safety training and the development of a plan to investigate accidents to prevent future injury; consequently, there are companies that not only possess such controls but that point them out as much as possible, in order to give them greater relevance among companies that work transparently and wish to gain greater legitimacy [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent accidents, exhaustive maintenance is necessary along with periodic safety inspections, continuous safety training and the development of an accident investigation plan [ 27 ]. Therefore, there are a wide variety of works that investigate the causes of construction accidents and affect the safety of workers, such as the company size, its safety policy, the attitude of workers, preventative coordination at the project and execution phase of the planned work [ 15 , 28 , 29 ], and safety management in the company [ 26 , 28 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification and analysis of accident factors is an important area of scientific research, as it is the basis for the proper design and planning of training and preventive actions, which in turn leads to reduced accidents at work [10,[12][13][14][15][16][17].…”
Section: Literature Surveymentioning
confidence: 99%
“…The authors of the studies published in [12] emphasize that all participants of a project, as well as the environmental conditions in which the construction is carried out, are responsible for occupational accidents. In papers [13,14], a significant number of accident factors were identified, which were then classified into five groups related to: clients, consultants, contractors, construction workers and construction sites. Among the identified factors, the most important factors were deficiencies in the personal equipment of employees, a defective technical condition of devices, a lack of training, and also inappropriate use of building materials and devices.…”
Section: Literature Surveymentioning
confidence: 99%
“…Additionally, Gyi, D. et al even [8] published a study, showing that there is a consistent and integrated approach necessary to measure safety and health performance for accidents avoidance at contraction site. Even in newer research results the issues for safety and health problems in construction industry is a topic [9], which proofs that up to now there are no sufficient solutions existing. Therefore, the authors proposes a capacitive ECG system that can be used to identify dangerous symptoms, which could distract the operator, or warn from a potential upcoming unconsciousness, and thereby support the accidence avoidance on construction site.…”
Section: Introductionmentioning
confidence: 99%